Implementasi Lesson Study Pada Mata Kuliah Konsep Dasar Matematika di Program Studi PGSD FKIP Universitas Negeri Malang - Ahyansyah, Ahyansyah; Mawaddah, Sukma; Hastuti, Intan Dwi; Sutarto, Sutarto (Yayasan Pendidikan Intan Cendekia, 2022)
This article aims to describe the implementation of lesson study in the basic concepts of mathematics at the PGSD Study Program, University of Muhammadiyah Mataram. Data collection techniques used in this study were interviews, documentation, and observation. The data that has been collected was analyzed using qualitative descriptive data analysis. The implementation of this lesson study uses three stages, namely plan, do, and see. Lesson study implementation activities were carried out in the Department of Elementary School Teacher Education (PGSD) with a sample of 37 PGSD students in the first semester of basic mathematics concepts. The plan activities consist of (1) determining the lesson study team, determining the model lecturer, determining the observer, and making the lesson study observation sheet; (2) determining the supervising lecturers, determining lesson study practice classes, determining lesson study teaching practice schedules and (3) designing learning tools (RPP, materials, learning media, LKM). Do activities consist of preliminary activities, core activities and closing activities. While the see activity discusses the advantages and disadvantages of the do activities that have been carried out both from the civil servant lecturer, observation 1 and observer 2.